2014
DOI: 10.1016/j.jcin.2013.12.203
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Beam Angulation and Radiation Exposure in the Cardiac Catheterization Laboratory

Abstract: This study uniquely describes radiation dosimetry using contemporary equipment in a real-world setting. Extreme angulations were associated with high air kerma values. Fluoroscopy compared with acquisition was more sensitive to changes in angulation, with relatively larger increases in total air kerma with small increases in steepness of the angulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 15 publications
4
55
0
Order By: Relevance
“…One of the most important procedure-related factors governing the amount of radiation scattered is the beam orientation. Previous studies [17] showed that all extreme projections were associated with a particular high degree of Air Kerma rates and in particular in left caudal and right caudal. Kuon et al [18] showed that during transfemoral approach the left caudal view resulted in as much radiation exposure to the interventionalist as a left cranial view.…”
Section: Discussionmentioning
confidence: 84%
“…One of the most important procedure-related factors governing the amount of radiation scattered is the beam orientation. Previous studies [17] showed that all extreme projections were associated with a particular high degree of Air Kerma rates and in particular in left caudal and right caudal. Kuon et al [18] showed that during transfemoral approach the left caudal view resulted in as much radiation exposure to the interventionalist as a left cranial view.…”
Section: Discussionmentioning
confidence: 84%
“…17 The relative contribution of each of the above elements in the reduction of operator radiation exposure observed in RadiCure cannot be determined; however, fluoroscopy time was numerically lower in the Bleeper Sv group, whereas use of disposable radiation shields was similar in the 2 study groups. Image intensifier angulation can significantly affect radiation scatter, 18 and part of the operator radiation reduction shown in RadiCure may have resulted from repositioning the C-arm to less angulated projections.…”
Section: Discussionmentioning
confidence: 99%
“…First operator radiation exposure was lower in the Bleeper Sv group both for diagnostic angiography (7 [4][5][6][7][8][9][10][11] versus 10 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] μSv; P<0.001) and for PCI (11 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] versus 14 [6][7][8][9][10][11][12][13][14][15][16][17]…”
Section: Procedural Outcomesmentioning
confidence: 99%
“…Based on our observations of factors that govern radiation dosimetry, 20 we developed this initiative toward radiation dose reduction. The components of this initiative included the following measures:…”
Section: Radiation Dose Reduction Initiativementioning
confidence: 99%
“…lower dose x-rays. [17][18][19] Based on our observations of factors that govern radiation dosimetry, 20 we developed a comprehensive initiative toward radiation dose reduction.…”
mentioning
confidence: 99%